Healthcare workers’ attitudes and factors affecting provision of sexual and reproductive health services to adolescents in refugee settlements, Western Uganda - Mambo, Simon Binezero; Lodhi, Moazzam Mohiuddin; Asiimwe, Isa; Bizimana, Gloria Neema; Makelele, Amos M’yisa; Mbina, Solomom Adomi; Igwe, Mathew Chibunna; Ibrahim, Umar (Frontiers in Reproductive Health, 2025)
BackgroundProvision of sexual and reproductive health services has an important impact on the adolescents standard of life. Healthcare workers interactions with clients has been highlighted as one of the main barriers keeping adolescents from seeking sexual and reproductive health services. This study aimed to assess the Healthcare workers’ attitudes and factors affecting provision of sexual and reproductive health services in the Nakivale, Kyaka II, and Rwamwanja refugee settlements.MethodsThis was a cross-sectional quantitative study in which healthcare workers from public and private health facilities refugee communities in south-western Uganda responded to a questionnaire. Binary logistic regression was done to assess the baseline characteristics associated with provision of these services using SPSS version 26.ResultsOf the 386 medical professionals enrolled, 194(50.3%) were females with a mean age of 30.9 years (SD = 6.9). The services that were most commonly offered were contraception counselling/provision (81.3%) and comprehensive sexuality education provision (75.1%). The least offered services were safe abortion care (40.9%). The good attitudes were highest towards comprehensive sexuality education and antenatal, intrapartum plus postnatal care while the bad attitudes were highest toward safe abortion care. Residence, designation and type of facility had a significant association with offering of the different services (P < 0.05 for all at multivariate level of analysis). Being from rural area was positively associated with ASRH services (cOR = 2.685, 95% CI = 1.414–5.098). Being a nurse was associated with reduced provision of services as compared to being a counselor (cOR = 0.295, 95% CI = 099–0.882). Government facilities were more likely to offer adolescent sexual and reproductive health services compared to private facilities (cOR = 2.155, 95% CI = 1.169–4.075).ConclusionIn this study, majority of the study participants had a good attitude towards comprehensive sexuality education provision and antenatal, intrapartum and postnatal care while the bad attitudes were highest toward safe abortion care. More efforts are still required toward provision of safe abortion care and harmful traditional practices prevention. This will be achieved by providing training which will be vital in improving knowledge and attitude toward these services. The training should be more focused on the older professionals and non-councilors.